Subduction Initiation at the Corner of Small Oceanic Basins - Miao Dong; Tianyao Hao; Yue Li; Jian Zhang; Gui Fang (Geophysical Research Letters)
Abstract In Southeast Asia, emerging subduction zones often appear to begin at the corners of small oceanic basins, which have a triangular‐indenter continent–ocean boundary geometry. To investigate the influence of a triangular corner on subduction initiation, we performed a series of three‐dimensional numerical simulations with varying corner angles and base lengths. The results show that the apex of the corner constitutes the initial location of subduction, irrespective of the angle or the extent of the corner. Smaller angle corners are more likely to facilitate subduction initiation. At the same time, wide acute angle corners are difficult to form. Our findings suggest that triangular corner structures may facilitate subduction initiation in smaller basins; however, the role such corners in subduction initiation is limited in larger basins. Our results emphasize the importance of accounting for the three‐dimensional geometry of a subduction zone when examining its subduction dynamics and geological features.